Compensation policies and comparative capitalisms - Suleman, F.; Duarte, H.; Brewster, C.; Suleman, A. (European Journal of Industrial Relations, 2022)
A widespread rhetoric suggests that market-like rules dominate employment relationships, and particularly compensation, but empirical evidence is inconclusive. This research examines organisations’ compensation policies in clusters of European capitalist economies to test such a hypothesis. Four fuzzy clusters emerged from data, namely, Standard, Internalised, Competitive and Incentive, which illustrates a division between organisation- and market-based models. Collective pay rules characterise organisation-based model, and this is the predominant model in all countries except for the liberal market economies. Firms from different models of capitalism rely on internal labour market pay rules, suggesting that the scope of the liberal market system is narrow. Differences within clusters of capitalist economies suggest a role for agency and hidden labour market specificities in each grouping. The similarities of pay policies open room to identifying capitalist economies differently.